2004
DOI: 10.1159/000078618
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sclerectomy with Various Implants: An Experimental and Histopathologic Study in a Rabbit Model

Abstract: Background and Objective: To investigate the effectiveness of various implants used in experimental deep sclerectomy and to report tissue reactions developed to these implants histopathologically. Materials and Methods: Forty eyes of 40 New Zealand white albino rabbits underwent deep sclerectomy with various implants. The rabbits were divided into four groups; each consisted of 10 eyes. Deep sclerectomy was performed using copolymer materials in group 1, silicone materials in group 2 and chromic catgut suture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Hyphaema, being an intraoperative complication [8], was present in only one of the eight animals which is comparable with the hyphaema rates reported by Erkiliç et al [47] who performed deep sclerectomy with various implants (copolymer materials, silicon tubes, chromic catgut suture pieces). It must be taken into account that the complication of hyphaema is mostly dependent on the surgical techniques [11].…”
Section: Discussionsupporting
confidence: 78%
“…Hyphaema, being an intraoperative complication [8], was present in only one of the eight animals which is comparable with the hyphaema rates reported by Erkiliç et al [47] who performed deep sclerectomy with various implants (copolymer materials, silicon tubes, chromic catgut suture pieces). It must be taken into account that the complication of hyphaema is mostly dependent on the surgical techniques [11].…”
Section: Discussionsupporting
confidence: 78%
“…They stated that the implant dissolved within 6–9 months and was replaced by new autologous scleral tissue, which formed a tunnel. In a study on an animal model, it was observed that non‐absorbable implants may fix the intrascleral space better than absorbable implants 43 . But T‐flux occupies a determined volume within the scleral lake.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on an animal model, it was observed that non-absorbable implants may fix the intrascleral space better than absorbable implants. 43 But T-flux occupies a determined volume within the scleral lake. This may cause a decrease in the volume of lake and in the success rates when compared with cases in which SKgel implant were used.…”
Section: E204mentioning
confidence: 99%
“…In clinical evaluations the following endpoints were taken into consideration: pupil reaction to the light, light intolerance, leakage from conjunctival sac, swelling and inflammation of concjunctiva, sclera swelling and redness in wound area, postoperative scleral adhesions, time of wound healing and clinical status of the eyeball after 1 month observation. For evaluation of clinical lesions and wound healing the modified 4-graded scoring system (0-3) was adopted according to Hoekzem [18] and Erkiliç [19] (Table 1). …”
Section: Methodsmentioning
confidence: 99%